Analisa Kesukaan Produk Balsem Aroma Bunga - Warditiani, NK; Arisanti, CIS; Swastini, DA; Wirasuta, IMAG (Jurnal Farmasi Udayana, 2020)
Balm is a thick oil containing resin oil and essential oils, feels hot. Balm is applied by rubbing and rubbing on the skin. The balm has the benefit of reducing muscle aches, which are caused by the burning sensation of the balm. Essential oils can cause a refreshing and soothing sensation after the use it. This balm can calm consumers who experience muscle pain. The aim of this study is to find out the best formula preferred by consumers aged 20 to 60 years. The method of this study is a qualitative analysis, based on the answers of questionnaires by respondent. Four balm formula was tested, namely Balm no 1, Balm no 2, Balm no 3, Balm no 4. The parameter assessed is aroma, texture, color and warm sensation. The results show that the description of male consumers (54.5%), women (45.5%), ages 20-30 years (45.5%), ages 31-40 years (27.3%), ages 41-50 years (18.2%), aged 51 years and over (9%). The results showed that most respondent liked Balm No. 4, both in terms of aroma, texture, color and warm sensation. It is expected that this warm feeling will be able to reduce the aches in the muscles of respondent.